Aristolactams and Alkamides of Aristolochia gigantea - Holzbach, Juliana C. [UNESP] (2010)
A new aristolactam, aristolactam 9-O-beta-D-glucopyranosyl-(1 -> 2)-beta-D-glucoside, and two alkamides, N-cis- and N-trans-p-coumaroyl-3-O-methyldopamine, were isolated from stems of Aristolochia gigantea, together with the known compounds allantoin, E-nerolidol, beta-sitosterol, (+)-kobusin, (+)-eudesmin, trans-N-feruloyltyramine, trans-N-coumaroyltyramine, trans-N-feruloyl-3-O-methyldopamine, aristolactam Ia-N-beta-D-glucoside, aristolactam Ia 8-beta-D-glucoside, aristolactam IIIa, and magnoflorine. Their structures were determined by spectroscopic analyses.